1997
DOI: 10.1021/jp9701146
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Reactions of ClONO2with Cl-(D2O)n=0-3and NO2-

Abstract: The reactions of ClONO 2 with the Cl -(D 2 O) ne3 and NO 2 -ions were studied in a flow-tube apparatus at several temperatures in the range 170-298 K and at a helium buffer gas pressure of 0.28 Torr. Rate constants for these reactions were determined, establishing that all these ions react quite efficiently with ClONO 2 . The product ions observed in reaction sequences are reported, and reaction mechanisms are proposed to account for the findings. In the case of Cland NO 2 -the main product ion is NO 3 -, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…This reaction has been shown to be thermodynamically favorable in the gas phase. 44 Wincel et al 30 have also shown reaction 3 to occur efficiently at temperatures…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This reaction has been shown to be thermodynamically favorable in the gas phase. 44 Wincel et al 30 have also shown reaction 3 to occur efficiently at temperatures…”
Section: Introductionmentioning
confidence: 95%
“…6,[13][14][15][16][17][18][19][20][21][22] The availability of modern laboratory apparatus allows the control of experimental parameters such as reactant partial pressure and substrate temperature so that conditions close to stratospheric ones can be simulated. Hanson,18,[22][23][24] Zhang,25,26 and other workers [19][20][21][27][28][29][30] have used flow tubes to measure reaction probabilities or sticking coefficients (γ). The hydrolysis reaction and to a somewhat lesser extent, the direct reaction, have been extensively studied by the complementary techniques of Fourier transform (FTIR) or reflection-absorption infrared spectroscopy (RAIR) and mass spectrometric (MS) methods.…”
Section: Introductionmentioning
confidence: 99%
“…21 The reactions of NO 2 with the related and atmospherically important chlorine nitrate, ClONO 2 , have also been characterized by flow tube techniques. 22 Reactions of gas-phase common nucleophiles are of particular interest, among other reasons, because they bear direct resemblance to common reactions of alkyl nitrates in solution. 23 The first gas-phase report claimed that ethyl nitrate reacts with anions such OH -, C 2 H 5 Oand C 2 H 3 Oalmost exclusively to yield the nitrate ion, NO 3 -.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase reactions of NO 2 − with alkyl nitrates have been shown to yield NO 3 − by a termolecular displacement process, and to promote association with the parent neutral under high pressure mass spectrometry conditions . The reactions of NO 2 − with the related and atmospherically important chlorine nitrate, ClONO 2 , have also been characterized by flow tube techniques …”
Section: Introductionmentioning
confidence: 99%
“…A particularly interesting benchmark for testing hybrid QM-CM schemes consists of the investigation of chemical reactivity in aqueous clusters. In recent years, these systems have attracted the attention of many experimental and theoretical 19-21 groups, due to the peculiar properties of the water substance and their relevance in atmospheric and environmental chemistry. In most of the currently employed hybrid schemes, the dynamics that governs the electronic charge distribution of the QM subsystem is performed within the adiabatic approximation, i.e., assuming an immediate adjustment of the electronic density of the quantum subsystem to the instantaneous ground-state potential energy surface generated by a given nuclear configuration.…”
Section: Introductionmentioning
confidence: 99%